G Protein-Coupled Receptors As Regulators of Localized Translation: The Forgotten Pathway? - Tréfier, Aurélie; Pellissier, Lucie P.; Musnier, Astrid; Reiter, Eric; Guillou, Florian; Crépieux, Pascale (Frontiers in Endocrinology, 2018)
G protein-coupled receptors (GPCR) exert their physiological function by transducing a complex signaling network that coordinates gene expression and dictates the phenotype of highly differentiated cells. Much is known about the gene networks they transcriptionnally regulate upon ligand exposure in a process that takes hours before a new protein is synthesized. However, far less is known about GPCR impact on the translational machinery and subsequent mRNA translation, although this gene regulation level alters the cell phenotype in a strikingly different timescale. In fact, mRNA translation is an early response kinetically connected to signaling events, hence it leads to the synthesis of a new protein within minutes following receptor activation. By these means, mRNA translation is responsive to subtle variations of the extracellular environment. In addition, when restricted to cell sub-cellular compartments, local mRNA translation contributes to cell micro-specialization, as observed in synaptic plasticity or in cell migration. The mechanisms that control where in the cell an mRNA is translated are starting to be deciphered. But how an extra-cellular signal triggers such local translation still deserves extensive investigations. With the advent of high-throughput data acquisition, it now becomes possible to review the current knowledge on the translatome that some GPCRs regulate, and how this information can be used to explore GPCR-controlled local translation of mRNAs.